ON PROPERTIES OF PRIME IDEAL GRAPHS OF COMMUTATIVE RINGS - Kurnia, Rian; Abrar, Ahmad Muchlas; Syarifudin, Abdul Gazir; Wijaya, Verrel Rievaldo; Supu, Nur Ain; Suwastika, Erma (PATTIMURA UNIVERSITY, 2023)
The prime ideal graph of in a finite commutative ring with unity, denoted by , is a graph with elements of as its vertices and two elements in are adjacent if their product is in . In this paper, we explore some interesting properties of . We determined some properties of such as radius, diameter, degree of vertex, girth, clique number, chromatic number, independence number, and domination number. In addition to these properties, we study dimensions of prime ideal graphs, including metric dimension, local metric dimension, and partition dimension; furthermore, we examined topological indices such as atom bond connectivity index, Balaban index, Szeged index, and edge-Szeged index.